Single Stage Surgery for Open Lisfranc Injury: A Case Report - Lakhey, Rajesh B; Bhandari, Prawesh S; KC, Govinda (Journal of Institute of Medicine Nepal, 2021)
Management of open Lisfranc injuries is challenging. The improper management of the injuries might lead to bad results like skin necrosis and arthritis of Lisfranc’s joints. A case of Myerson type A Gustilo Grade IIIB open Lisfranc injury was managed with single stage debridement and internal fixation. At three years follow-up, the result was excellent with American Orthopedic Foot and Ankle Society (AOFAS) midfoot score of 100 and the patient had rejoined his previous occupation requiring prolonged walking.